TIPOLOGI PERUBAHAN RUANG PADA RUMAH PANGGUNG MASYARAKAT DESA PAGAR DEWA KECAMATAN WARKUK RANAU SELATAN - Muhammad Agung Kurnain; Edward Pandelaki; Agung Dwiyanto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The house is the result of the culture of an ethnic group which produces specific dwellings based on tradition in the process of its formation. One manifestation of this cultural product is the Stilt House of the Ranau community, which is one of the tribes in South Sumatra Province, which is located in Pagar Dewa Village, Warkuk Ranau Selatan, Ogan Komering Ulu Selatan District. The people of the Pagar Dewa Village Stilt House are currently experiencing changes in space in the area below the house and the area above the house which forms a new spatial pattern with various factors causing the changes. The purpose of this study was to determine the typographical form of changes in the space on stilts in the Pagar Dewa village community, to determine the factors causing the changes in space and to categorize the forms of changes in space into several types of changes. This research uses a qualitative approach with descriptive methods. For the sampling technique, the sample was taken purposively random, with the Quota Sampling model, namely determining the leading key area and the key group (respondents) determined based on the hamlet that became the first hamlet to start civilization in Pagar Dewa Village (Dusun I), a hamlet that has educational facilities, bridges and other facilities. Religious (Dusun II), a hamlet that has a direct orientation towards the river and rice fields (Dusun VII). In this study, 3 forms of typography were obtained from the changes in the space on the stilt houses of the Pagar Dewa village community.Keyword: Tipology, Transformasion of Space, Stilt HouseAbstrak: Rumah merupakan sebuah hasil kebudayaan sebuah suku bangsa yang menghasilkan hunian yang spesifik berdasarkan tradisi dalam proses pembentukannya. Salah satu wujud dari hasil kebudayaan tersebut adalah Rumah Panggung masyarakat Ranau yang merupakan salah satu suku di Provinsi Sumatera Selatan yang berada di Desa Pagar Dewa Kecamatan Warkuk Ranau Selatan Kabupaten Ogan Komering Ulu Selatan. Rumah Panggung masyarakat desa Pagar Dewa saat ini banyak yang mengalami perubahan ruang pada area bawah rumah dan area atas rumah yang membentuk sebuah pola ruang baru dengan berbagai factor penyebab perubahannya. Tujuan dari penelitian ini adalah untuk mengetahui bentuk tipologi perubahan ruang rumah panggung masyarakat desa Pagar Dewa, mengetahui faktor penyebab perubahan ruang dan mengelompokan bentuk perubahan ruang tersebut menjadi beberapa tipe perubahan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik sampling Sampel diambil secara purposive random, dengan model Quota Sampling yaitu menetapkan terdahulu key area dan key group (responden) ditentukan berdasarkan Dusun yang menjadi Dusun Pertama memulai peradaban di Desa Pagar Dewa (Dusun I), Dusun yang memiliki fasiltas Pendidikan, Jembatan dan fasilitas Keagamaan (Dusun II), Dusun yang memiliki orientasi langsung ke arah sungai dan sawah (Dusun VII ). Pada penelitian ini mendapatkan 3 bentuk tipologi perubahan ruang rumah panggung masyarakat desa Pagar Dewa.Kata Kunci: Tipologi, Perubahan Ruang, Rumah Panggung